POLIGAMI DALAM PERSPEKTIF AL-QUR’AN DAN KOMPILASI HUKUM ISLAM (TINJAUAN TAFSIR MAQASHIDI DAN HEURMENETIKA) - Suriadi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
Polygamy is not merely a product of Islam but has existed since pre-Islamic times. Islam came not to start polygamy but to regulate how polygamy should be carried out. In the teachings of Islam, the Al-Quran is a guide for mankind in which there are rules from various aspects of human life, one of which regarding polygamy has been regulated in Surah An-Nisa verses 1-4 and Surah An-Nisa verse 129 , which in interpreting polygamy, the scholars differed in interpreting the verses of polygamy. The differences in these types of interpretation are solely to reveal the meaning of the verse. Likewise, in reality, society is no exception in Indonesia, which, although basically the regulation adheres to the principle of monogamy in marriage. However, under certain conditions, the court can grant permission to a husband to have more than one wife if desired by the party concerned. The application of polygamy itself needs to look at the criteria for the conditions of those who are allowed to do polygamy so that it does not cause harm in the future.